IL-1 receptor blockade alleviates endotoxin-mediated impairment of renal drug excretory functions in rats - Kadova, Zuzana; Dolezelova, Eva; Cermanova, Jolana; Hroch, Miloš; Laho, Tomas; Muchova, Lucie; Staud, Frantisek; Vitek, Libor; Mokry, Jaroslav; Chladek, Jaroslav; Havlinova, Zuzana; Holecek, Milan; et al. (American journal of physiology. Renal physiology, 2015)
The aim of our study was to investigate whether two potent anti-inflammatory agents, dexamethasone and anakinra, an IL-1 receptor antagonist, may influence acute kidney injury (AKI) and associated drug excretory functions during endotoxemia (LPS) in rats. Ten hours after LPS administration, untreated endotoxemic rats developed typical symptoms of AKI, with reduced GFR, impaired tubular excretion of urea and sodium, and decreased urinary excretion of azithromycin, an anionic substrate for multidrug resistance-transporting proteins. Administration of both immunosuppressants attenuated the inflammatory response, liver damage, AKI, and increased renal clearance of azithromycin mainly by restoration of GFR, without significant influence on its tubular secretion. The lack of such an effect was related to the differential effect of both agents on the renal expression of individual drug transporters. Only dexamethasone increased the urinary clearance of bile acids, in accordance with the reduction of the apical transporter (Asbt) for their tubular reabsorption. In summary, our data demonstrated the potency of both agents used for the prevention of AKI, imposed by endotoxins, and for the restoration of renal drug elimination, mainly by the improvement of GFR. The influence of both drugs on altered tubular functions and the expression of drug transporters was differential, emphasizing the necessity of knowledge of transporting pathways for individual drugs applied during sepsis. The effect of anakinra suggests a significant contribution of IL-1 signaling to the pathogenesis of LPS-induced AKI.
Keywords: xenobiotika; Animals; antiflogistika; lipopolysacharidy; Rats, Wistar; endotoxemie; akutní poškození ledvin; endotoxiny; Glomerular Filtration Rate; Endotoxemia; Azithromycin; Immunosuppressive Agents; Anti-Bacterial Agents; Lipopolysaccharides; Renal Elimination; azithromycin; Endotoxins; Interleukin 1 Receptor Antagonist Protein; Male; Xenobiotics; dexamethason; Anti-Inflammatory Agents; Dexamethasone; antagonista receptoru pro interleukin 1; eliminace ledvinami; zvířata; mužské pohlaví; Acute Kidney Injury; antibakteriální látky; imunosupresiva; hodnoty glomerulární filtrace; potkani Wistar